Application of the Method of Problem Learning in the Study of the Discipline “Information Security” - V. A. Sizov; D. M. Malinichev; Kh. K. Kuchmezov; V. V. Mochalov (Открытое образование (Москва))
The purpose of this article is to develop students’ critical thinking for solving problems in the field of information security by using the method of problem learning in teaching the discipline “Information Security”. The role of this method in the development of critical thinking, research creativity of students and their achievement of a better understanding of educational material in the field of information security is emphasized.Materials and research methods. The main conditions for the effectiveness of problem learning in the study of the discipline “Information Security” are highlighted by the method of analysis of the subject area: motivation of students, the feasibility and significance of problem situations offered to students on various aspects of information security, dialogical friendly communication between lecturer and students. As research materials, an example of using the method of problem learning in solving the task of information protection in state information systems with terminal access devices is considered. The example presents the problem of increasing the efficiency of information protection in state information systems with terminal access devices, i.e. state information systems using the “thin client” architecture, as well as a way to solve it by assessing threats and improving the relevant mechanisms for ensuring information security, presented in the regulatory documents governing the requirements for information protection in state information systems with terminal access devices. Results. The paper considers the practical task of creating and resolving a problem situation for the protection of information in state information systems with terminal access devices, which can be used in the educational process to solve similar tasks by the method of problem learning.The creation of a problematic situation is based on the existing contradictions in the regulations governing the functioning and protection of information of this type of systems in which the protected information is processed in order to comply with legislation and ensure the functioning of authorities. As a result of using a systematic approach, which involves considering the process of information protection in the form of a set of stages in the formation of requirements for state information systems using the architecture of the “thin client”, improving the regulatory framework, the trainees form proposals for the protection of information in state information systems using the architecture of the “thin client” to ensure the design security of state information systems, taking into account the complex of urgent threats to information security. The presented solution to the problem situation in the considered task requires from the trainees general cultural competencies, such as: identifying contradictions, colliding opposing points of view, comparing facts, considering the problem from different points of view, generalizing, concretizing facts, etc.Conclusions. Thus, the paper substantiates the method of problem learning in the study of the discipline “Information Security” and presents an example of its use in solving the problem of information protection in state information systems with terminal access devices. As a result, the trainees must identify threats that are absent in the information security threat databank of the Federal Service for Technical and Export Control of the Russian Federation (FSTEC of Russia) and determine the directions for further development of information security and information protection in state information systems with terminal access devices. The practical solution of this problem by a group of students within the framework of the study of the discipline “Information Security” showed a high level of competence development.